Efficacy of PPV Combined with Air Tamponade for Treatment of Inferior Retinal Breaks - Yong Zhang; Xin Li; Guiping Pan; Zhen Tian; Siwei Liu; Jun Yuan (Journal of Ophthalmology)
Purpose. To observe the efficacy and safety of pars plana vitrectomy (PPV) combined with filtered air tamponade in the treatment of rhegmatogenous retinal detachment (RRD) with inferior retinal breaks. Methods. This retrospective study included 20 patients (20 eyes) with inferior retinal breaks in RRD; all underwent PPV combined with filtered air tamponade. Preoperative examinations included BCVA, IOP, anterior segment, fundus and locations, numbers, and sizes of retinal breaks and ocular B-mode ultrasonography. Postoperative examinations included BCVA, IOP, residual gas volume, retinal reattachment, and complications. Results. After follow-up for 1 year, the primary retinal reattachment rate was 95% and the final reattachment rate was 100%. Pre- and postoperative BCVA averaged 1.51 ± 0.63 and 0.97 ± 0.58 logMAR, respectively; the difference was statistically significant (P<0.001). Average pre- and postoperative IOP were not statistically different. The average volume of residual gas on the first day after the surgery was 77.5%; the gas was absorbed in all patients within 2 weeks; no significant postoperative complications were observed. Conclusion. PPV combined with filtered air tamponade is a safe and effective treatment for RRD with inferior retinal breaks. Notably, the retinal reattachment rate is high, gas absorption is rapid, and incidence of complications is low.